МОНГОЛ, ЯПОН УЛСЫН ХООРОНД ДИПЛОМАТ ХАРИЛЦАА ТОГТСОН НЬ (1972 он ) - Д. Бумдарь (Politology, 2023)
This article traces historical terms of Mongolia-Japan’s diplomatic relationship and emphasizes mutual understanding and cooperation especially sphere of economic, social, cultural relations of the two countries. This article surveys official treaty and agreements, projects and programs, furthermore to define the result of official visits by the leaders of those two countries. Therefore, emphasizes further diplomatic and strategic relations between Mongolia and Japan.